Effect of mismatching currents on performance of differential relay (87) / Ali Asghar Fathollahi Fard - Fard, Ali Asghar Fathollahi (2006)
Transformers need to be protected not only from internal short circuits, but also from abnormal operating Conditions, such as over loading, inrush currents, go-through faults and surges. The simplest but extremely effective form of protection is the electromechanical relay, which closes contacts and hence energizes the circuit-breaker opening mechanisms when currents larger than allowed values pass through. In a power system, the differential relay should operate only in its indicated protection zone, and not for out of its protection zone. This paper will focus on the problem, where the differential relay (87) indiscriminately functions for its out of protection zone. Effect of mismatching currents has been considered.